Analysis of Land Cover Transformation within the Protected Peatland Area of Ambawang Village Forest, Kubu District, West Kalimantan - Nurdien Nansyah; Ulul Hidayah; Farisa Maulinam Amo (Jurnal Perencanaan Wilayah dan Kota, 2026)
The Regional Regulation of West Kalimantan Province prohibits new land opening in the peat ecosystem area until zoning for the area's protection and cultivation functions has been determined for specific plants. Based on the 2022 satellite image maps overlaid with the boundaries of the Ambawang Village Forest, it is known that 309.7 hectares of land have been cleared, thereby reducing the area's primary function. This research aims to determine when land cover changes occur in the peat ecosystem of the Ambawang Village Forest. The required data are field survey data, satellite imagery maps from 2004, 2009, 2016, and 2022, a map of the West Kalimantan terrain, an indicative map of production forest utilization directions for 2021, and the boundaries of the Ambawang Village Forest map. The analytical method used is a descriptive analysis with a spatial approach. The result indicates that between 2004 and 2016, there was a change in land cover from medium-density secondary swamp/peat forest to non-forest (deforestation) covering an area of 309.7 hectares. Between 2009 and 2016, forest land continued to be cleared to make way for natural/semi-natural open areas, shrublands, and oil palm plantations. From 2016 to 2022, forest clearing ceased, the area of oil palm plantations remained constant, and shrubland increased. It shows there is no violation of the West Kalimantan Province Regional Regulation number 8 of 2021, as the forest land was cleared before this regulation was enacted.